2012
DOI: 10.1515/jnetdy-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

A non-equilibrium thermodynamics model of multicomponent mass and heat transport in pervaporation processes

Abstract: The framework of non-equilibrium thermodynamics (NET) is used to derive heat and mass transport equations for pervaporation of a binary mixture in a membrane. In this study, the assumption of equilibrium of the sorbed phase in the membrane and the adjacent phases at the feed and permeate sides of the membrane is abandoned, defining the interface properties using local equilibrium. The transport equations have been used to model the pervaporation of a water-ethanol mixture, which is typically encountered in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This occurs by evaporation on one side and condensation on the other side, resulting in selective fluid transport across the vapor gap away from the contaminated fluid. [9][10][11] This mode of transport is only possible when the pores of the membrane repel the liquid sufficiently so as to promote the phase transition. A phase-transition will be enforced inside, but also outside, the pore depending on the size of the liquid-wall contact angle.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs by evaporation on one side and condensation on the other side, resulting in selective fluid transport across the vapor gap away from the contaminated fluid. [9][10][11] This mode of transport is only possible when the pores of the membrane repel the liquid sufficiently so as to promote the phase transition. A phase-transition will be enforced inside, but also outside, the pore depending on the size of the liquid-wall contact angle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the coupling between mass and heat transfer, more specifically, mass transfer driven by temperature gradients (Soret effect), and heat transfer driven by concentration gradients (Dufour effect) is relatively straightforward to incorporate in this framework, both for in-plane transfer (equations ( 40) and ( 41)), and transfer across the interface (equations ( 43) and ( 44)). Whereas in bulk phase transfer these effects are rarely of any importance, for transfer across interfaces they are often not negligible [229][230][231][232][233]. Neglecting these couplings may lead to predictions for the transfer coefficients which differ from their actual value by more than an order of magnitude.…”
Section: Multiphase Heat and Mass Transfer Problemsmentioning
confidence: 99%
“…Entropy production in parallel and counter ow system [11] and relativistic binary mixtures [12] were presented incorporating the non-equilibrium transport equation. The ndings of the previous studies [1][2][3][4][5][6][7][8][9][10][11][12] revealed that the characteristics of heat transport for micro-scale analysis were di erent than those of macro-scale analysis. Therefore, micro-scale energy transport, incorporating the phonon radiative transport equation, becomes essential for the thermal analysis of thin lms.…”
Section: Introductionmentioning
confidence: 95%
“…Considerable research studies were carried out to examine energy transport at micro scale [1][2][3][4][5][6][7][8][9][10] and entropy generation [11,12]. The analytical solution for the phonon radiative transport equation was presented to demonstrate the functional relation between the phonon characteristics and the independent variables such as time and space [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation